ANTHROPOMORPHISM IN THE TALE OF BAYAN BUDIMAN - ESSY SYAM; QORI ISLAMI ARIS; YESSI RATNA SARI (State University of Medan, 2024)
This research analyzes the element of anthropomorphism in the classical Malay literary work entitled